An MHD Modeling of the Successive X2.2 and X9.3 Solar Flares of 2017 September 6 - Inoue, Satoshi; Bamba, Yumi (The Astrophysical journal, 2021)
The solar active region 12673 produced two successive X-class flares (X2.2 and X9.3) approximately 3 hr apart in 2017 September. The X9.3 flare was the largest recorded solar flare in Solar Cycle 24. In this study we perform a data-constrained magnetohydrodynamic simulation taking into account the observed photospheric magnetic field to reveal the initiation and dynamics of the X2.2 and X9.3 flares. According to our simulation, the X2.2 flare is first triggered by magnetic reconnection at a local site where at the photosphere the negative polarity intrudes into the opposite-polarity region. This magnetic reconnection expels the innermost field lines upward, beneath which the magnetic flux rope is formed through continuous reconnection with external twisted field lines. Continuous magnetic reconnection after the X2.2 flare enhances the magnetic flux rope, which is lifted up and eventually erupts via the torus instability. This gives rise to the X9.3 flare.